Study of Effect of Midazolam on the Dose of Propofol for Laryngeal Mask Airway Insertion in Children - Dr. Gandhi Jha, Dr. Aditi Yadav, Dr. Gayatri Kumari, Dr. Anoop Kumar Singh, (International Journal of Innovative Research in Medical Science, 2017)
The major responsibility of an anesthesiologist is to provide adequate respiration for the patient and the most vital element is providing respiration is the airway. No anesthetic is safe unless diligent efforts are devoted to maintain an intact function airway. In studies it has been found that adverse respiratory episodes were mainly due to inadequate ventilation, esophageal intubation and insufficient tracheal intubation.